Two kinds of moraic nasal in Ciyao - Larry M. Hyman (LibraryPress@UF, 1997)
A problematic issue in a number of Bantu languages concerns the phonological analysis of "preconsonantal nasality", i.e., the question of whether NC entities should be analyzed as single prenasalized consonants or as sequences of nasal + (homorganic) consonant. In this paper, the authors examine two kinds of moraic nasal---one syllabic, one not-in Ciyao, a Bantu language spoken in East Africa. They further demonstrate that there is a third type of preconsonantal nasality in Ciyao which is neither moraic nor syllabic.